Winning the Talent Shift - Aldrich, Berta (Ascent Audio, 2021)
Winning the Talent Shift: Three Steps to Unleashing the New High Performance Workplace envisions a world where companies are fully equipped to exceed the challenges posed by the new global marketplace. Berta Aldrich argues if companies want to achieve future success, they must redesign their talent strategy using three important steps proven to increase revenues, engage teams and leaders, and set companies on the path to industry leadership. Winning the Talent Shift leverages the latest empirical research, experiences from over 1,000 team members and executives, and leadership classes that have spanned the globe to candidly reveal actionable solutions to what is holding most companies back from high performance. This book will show how companies can retain their high performers who produce 2-500% more than an average employee but are more likely to leave today's organizations; select and retain the new, high performing leader; and identify and develop women and people of color who can be exceptional leaders. Perfect for boards, C-suite, and aspiring male and female high performers, Winning the Talent Shift bravely shows how to recognize barriers, replace them with high performance attributes, and redesign the workplace to create the potential for sustainable growth and industry leadership for years to come.
Online resource; Title from title page (viewed February 23, 2021)
Keywords: Audiobooks; Livres audio